DETERMINAN FAKTOR PENERIMAAN DAN KEMANDIRIAN KEUANGAN DAERAH DI KABUPATEN PINRANG SULAWESI SELATAN - Haeruddin Saleh; A. Arwinsyah Kaharuddin; Seri Suriani (Bina Ekonomi, 2020)
Pinrang Regency is an autonomous region and is given the right to manage potential economic resources as a source of regional financial revenue. This study aims to determine how much influence the revenue from the region's own revenue (PAD) as well as in the form of grants received from the center can have an influence on regional financial independence. In this study, descriptive quantitative tools were used, while data was obtained through surveys in the form of interviews and documentation of various information obtained from agencies (spelling) managing regional finances and district BPS, while analysis tools were Microsoft Office Excel and SPSS 23. an illustration that Local Original Income has a positive effect, meaning that with an increase in PAD, regional financial independence has also increased, for funding assistance (balance funds) does not have an effect on regional financial independence, this occurs because the large amount of balance funds means that a lot of dependence on funding assistance from the outside. As a recommendation, the regional government will further increase the revenue of PAD (Regional Original Revenue) through intensification of regional revenue sources such as taxes, levies and other revenues, so that financial independence can be achieved. Keywords: regional revenue; investation; and regional capabilities